System design, analysis, and experimental investigations of linear switched reluctance machines with double mover configuration - CV, Aravind; Misron, Norhisam; Saadha, Aminath; Azhar, F; Stonier, Albert Alexander; Shunmugham Vanaja, Dishore (SAGE Publications, 2023)
This paper proposes a new double mover configuration of a linear switched reluctance motor (LSRM). The proposed design is established for optimization of the motional forces and to ensure a high-grade electromechanical energy conversion process. The major drawback of the traditional linear machine is that its force densities within and throughout its area is produced in its radial direction of the yoke and does not contribute to its motion or twisting force of the rotor. If these normal forces happen to be in the direction of motion, a larger motional force profile for SRM is yielded. Based on these guidelines, a new LSRM is developed. In order to compare the energy conversion efficiency of LSRM with that of the conventional SRM, a finite element model is constructed. The proposed system is simulated using the FEM software and tested under four conditions. Further, an experimental prototype of the proposed machine is also developed and tested in the laboratory. The results obtained from the prototype indicate that the proposed geometry offers superior performance in terms of high-power density and higher percentage of the national forces.